Conditions for Maximum Operating Efficiency of a Multi-Junction Solar Cell and a Proton Exchange Membrane Electrolyser System for Hydrogen Production - Gies, Warren (Université d'Ottawa / University of Ottawa, 2020)
Hydrogen is a valuable and versatile energy currency; it may be produced by harvesting solar energy and later used as a fuel to generate electricity any time of the day. This energy transaction of solar energy to hydrogen is evaluated in this work by employing a one-to-one multi-junction solar cell to proton exchange membrane combined system in a laboratory setting. Both components of the system were commercially available. The energy conversion efficiency of each isolated system was first evaluated to determine the ideal operation conditions of each respective system. For input currents in the range of 60 mA to 440 mA, the proton exchange membrane converted electrical energy to chemical potential energy with an efficiency greater than 90%. The multi-junction solar cell reached efficiencies of up to 33% while under a solar concentration of 30 Suns. The current and voltage characteristics, which resulted in the optimal operation of the isolated systems did not align and therefore, both systems were not operating at their ideal operation conditions when in the combined system. The overall energy conversion efficiency of the system was measured to be at most 19.1% under 25 Suns, an efficiency higher than systems employing traditional silicon solar cells. It was theorized that if the two system were operating under ideal conditions, the overall energy conversion efficiency would be 30.3% between 10 and 15 Suns. Methods to align the ideal operation conditions of the two systems are presented.
Keywords: Solar; Hydrogen; Electrolyser; Efficiency; Multi-junction; Concentrator